Исследование проекции на ось 0z напряженности магнитного поля соленоида в конструкциях магнитострикционных преобразователей угловых перемещений - Воронцов, А. А.; Назаренко, А. В. (Видавництво НТУ "Дніпровська політехніка", 2020)
В данной статье подробно рассмотрен анализ основных параметров соленоида, влияющих на формирование магнитных полей, сформированных при протекании в среде волновода токового импульса. Проведено математическое моделирование магнитного поля соленоида при изменении координаты, отсчитанной по оси OZ от его центра для различных значений радиусов и длины соленоида

In given article the analysis of key parametres of the solenoid influencing formation of magnetic fields, generated is in detail considered at course in impulse environment. It is spent mathematical modelling of a magnetic field of the solenoid at change of the co‐ordinate counted on axis 0Z from its centre for various values of radiuses and length of the solenoid.
Research of the 0z‐axis projection of the magnetic field strength of the solenoid in the designs of magneto‐strict converters of angular displacements
Keywords: соленоид; напряженность магнитного поля; магнитное поле соленоида; зависимость напряженности от координаты Z; the solenoid; intensity of a magnetic field; solenoid magnetic field; dependence of intensity on coordinate Z